Privileging industry : the comparative politics of trade and industrial policy - McGillivray, Fiona, 1967- (Princeton University Press, 2004)
The goal of this study is to explain when governments use trade and industrial policy for political goals, and to show why aiding an industry can be a politically efficient way for government to redistribute resources from one industrial sector to another.